Minocycline intra-bacterial pharmacokinetic hysteresis as a basis for pharmacologic memory and a backbone for once-a-week pan-tuberculosis therapy - Deshpande, Devyani; Srivastava, Shashikant; Pasipanodya, Jotam Garaimunashe; Gumbo, Tawanda (Frontiers in Pharmacology, 2022)
Background. There is need for shorter duration regimens for the treatment of tuberculosis, that can treat patients regardless of multidrug resistance status (pan-tuberculosis). Methods. We combined minocycline with tedizolid, moxifloxacin, and rifampin, in the hollow fiber system model of tuberculosis (HFS-TB) and mimicked each drugs’ intrapulmonary pharmacokinetics for 28 days. Minocycline-tedizolid was administered either as a once-a-week or a daily regimen. In order to explore a possible explanation for effectiveness of the once-a-week regimen, we measured systemic and intra-bacterial minocycline pharmacokinetics. Standard daily therapy (rifampin, isoniazid, pyrazinamide) was the comparator. We then calculated f or kill slopes for each regimen and ranked the regimens by time-to-extinction predicted in patients. Results. The steepest f and shortest time-to-extinction of entire bacterial population was with daily minocycline-rifampin combination. There was no difference in f between the minocycline-tedizolid once-a-week versus the daily therapy (p=0.85). Standard therapy was predicted to cure 88% of patients, while minocycline-rifampin would cure 98% of patients. Minocycline concentrations fell below minimum inhibitory concentration (MIC) after two days of once-weekly dosing schedule. The shape of minocycline intra-bacterial concentration-time curve differed from the extracellular pharmacokinetic system and lagged by several days, consistent with system hysteresis. Hysteresis explained the persistent microbial killing after HFS-TB concentrations dropped below the MIC. Conclusions. Minocycline could form a backbone of a shorter duration once-a-week pan-tuberculosis regimen. We propose a new concept of post-antibiotic microbial killing, distinct from post-antibiotic effect. We propose system hysteresis as the basis for the novel concept of pharmacologic memory, which allows intermittent dosing.